2017
DOI: 10.1111/hir.12183
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management in healthcare libraries: the current picture

Abstract: Knowledge management has seen something of a resurgence in attention amongst health librarians recently. Of course it has never ceased to exist, but now many library staff are becoming more involved in organisational knowledge management, and positioning themselves as key players in the sphere. No single model of knowledge management is proliferating, but approaches that best fit the organisation's size, structure and culture, and a blending of evidence based practice and knowledge sharing. Whatever it is call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Healthcare systems, as well as micro-level health facilities, generally depend on data and information collected by patients, medical doctors, or obtained from scientific studies [ 39 , 40 ]. In this context, management of information, knowledge creation and knowledge sharing, are key areas in the healthcare system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Healthcare systems, as well as micro-level health facilities, generally depend on data and information collected by patients, medical doctors, or obtained from scientific studies [ 39 , 40 ]. In this context, management of information, knowledge creation and knowledge sharing, are key areas in the healthcare system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This shift emphasised how evidence and knowledge could be used, the implicit and the tacit, to inform health care decisions. At the outset we were keen to build on the positive contribution librarians have made supporting evidence-based healthcare (Hopkins, 2017, p. 104). The aim was to extend beyond provision of information and evidence or just the management of knowledge.…”
Section: What Do We Mean By Knowledge Mobilisation?mentioning
confidence: 99%
“…The scoping review by Ma, Stahl, and Knotts (2018) described nine evolving and active roles, with embedded librarians as a strong theme. Several authors have identified external and occupational drivers of change, and discussed the need for the profession to respond (Brettle & Urquhart, 2011;Crum & Cooper, 2013;Henderson, 2014;Holst et al, 2009;Hopkins, 2017;King & Lapidus, 2015;McGowan, 2012;Murphy, 2013). Hallam et al (2010) concisely stated the challenges and outlook for the health librarian workforce: "Traditional library work is diminishing, professional boundaries are blurring, and emerging areas of work are being claimed by other professional groups" (p. 355).…”
Section: Literature Reviewmentioning
confidence: 99%